"Hard to reach, but not out of reach": Barriers and facilitators to recruiting Black African and Black Caribbean men with prostate cancer and their partners into qualitative research. (12th December 2018) - Bamidele, Olufikayo O.; E. McGarvey, Helen; Lagan, Briege M.; Chinegwundoh, Frank; Ali, Nasreen; McCaughan, Eilis
Abstract: Access and recruitment barriers may have contributed to the underrepresentation of Black African/Caribbean men and their partners in current psychosocial research related to prostate cancer survivors. Whilst some studies have explored recruitment barriers and facilitators from participants' perspectives, little is known from researchers' point of view. This paper aimed to address this gap in the literature. Recruitment strategies included the following: cancer support groups, researchers' networks, media advertisement, religious organisations, National Health Service hospitals and snowball sampling. Thirty‐six eligible participants (men = 25, partners = 11) were recruited into the study. Recruitment barriers comprised of gate‐keeping and advertisement issues and the stigma associated with prostate cancer disclosure. Facilitators which aided recruitment included collaborating with National Health Service hospitals, snowball sampling, flexible data collection, building rapport with participants to gain their trust and researcher's attributes. Findings highlight that "hard to reach" Black African/Caribbean populations may be more accessible if researchers adopt flexible but strategic and culturally sensitive recruitment approaches. Such approaches should consider perceptions of stigma associated with prostate cancer within these communities and the influence gatekeepers can have in controlling access to potential participants. Increased engagement with healthcare professionals and gatekeepers could facilitate better access to Black African/Caribbean populations so that their voices can be heard and their specific needs addressed within the healthcare agenda.